2018
DOI: 10.1001/jamaneurol.2017.4899
|View full text |Cite|
|
Sign up to set email alerts
|

Interpreting Genetic Variants in Titin in Patients With Muscle Disorders

Abstract: IMPORTANCE Mutations in the titin gene (TTN) cause a wide spectrum of genetic diseases. The interpretation of the numerous rare variants identified in TTN is a difficult challenge given its large size. OBJECTIVE To identify genetic variants in titin in a cohort of patients with muscle disorders. DESIGN, SETTING, AND PARTICIPANTS In this case series, 9 patients with titinopathy and 4 other patients with possibly disease-causing variants in TTN were identified. Titin mutations were detected through targeted rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
85
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 47 publications
3
85
0
1
Order By: Relevance
“…Clinically, four patients younger than five years old presented with delayed motor development since early infancy. Except for the 1‐year‐old infant who had basically normal muscle strengths, neck flexion weakness was prominent in the three other patients, which was in keeping with previous reports . Furthermore, rigid spine, contractures of Achilles, and high‐arched palate were all observed in these three patients, showing high clinical consistency in clinical phenotypes with a higher prevalence than previous reports .…”
Section: Discussionsupporting
confidence: 89%
“…Clinically, four patients younger than five years old presented with delayed motor development since early infancy. Except for the 1‐year‐old infant who had basically normal muscle strengths, neck flexion weakness was prominent in the three other patients, which was in keeping with previous reports . Furthermore, rigid spine, contractures of Achilles, and high‐arched palate were all observed in these three patients, showing high clinical consistency in clinical phenotypes with a higher prevalence than previous reports .…”
Section: Discussionsupporting
confidence: 89%
“…In the study by Savarese et al, 10 homology structural modeling analyses suggested deleterious consequence of missense variants 10 . The substitution p.(Thr6324Pro) is located on the external surface of a β strand in an Ig‐domain of the I‐band region, probably affecting the protein stability 10 . The missense variant p.(Thr31339Ala), located in an Fn3 domain within the A‐band, could affect hydrogen bonding with other molecules and may influence the interaction with titin ligands 10 .…”
Section: Discussionmentioning
confidence: 93%
“…In silico analyses suggested that the two missense mutations had deleterious consequences, based on their absence in the general population and the TITINdb predictions. In the study by Savarese et al, 10 homology structural modeling analyses suggested deleterious consequence of missense variants 10 . The substitution p.(Thr6324Pro) is located on the external surface of a β strand in an Ig‐domain of the I‐band region, probably affecting the protein stability 10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations